Apple turnover murder eaudiobook - Fluke, Joanne (Hannah Swensen Mystery, 2010)
Early summer brings plenty of work for baker Hannah Swensen, even before Mayor Bascomb's wife drops by The Cookie Jar to place an order for her charity event...For eleven-hundred cookies! And Hannah almost flips when her business partner, Lisa, suggests setting up an apple turnover stand. But she places her faith in Lisa and agrees to be a magician's assistant in the fundraiser's talent show. The only snag is the show's host, college professor Bradford Ramsey. Hannah and her sister, Michelle, each had unfortunate romances with Ramsey, and when the cad comes sniffing around between acts, Hannah tells him off. But when the curtain doesn't go up, she discovers Ramsey backstage - dead, with a turnover in his hand. Now Hannah must find a killer who's flakier than puff pastry - and far more dangerous.